PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE LEARNING CELL DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 RAO UTARA - Yunus, Muhammad; Rismen, Sefna; Pratiwi, Merina (Pendidikan Matematika, 2013)
This research was motivated by the importance of students understanding of mathematical concepts. This research aims to determine: 1) how the progress understanding indicators of students comprehension of mathematical concepts in class VIII SMPN 1 Rao Utara by applying active learning strategies questions students have type accompanied of quiz; 2) the studentsâ comprehension of mathematical concepts in class VIII SMPN 1 Rao Utara that apply active learning questions students have type accompanied of quiz was better than studentsâ comprehension of mathematical concepts that apply conventional learning. This design of this research was experiment with a random research on the subject. Population of this research was student`s at grade VIIIÂ  SMPN1 Rao Utara. Results of hypothesis testing with one side of t- test it was obtained that thitung was greather than ttabel, then the hypothesis in this research received. In conclusion, studentsâ comprehension of mathematical concepts that apply active learning The Learning Cell type accompanied by quiz was better than studentsâ comprehension of mathematical concepts that apply conventional learning.